Brand Trust Capacity in Mediating Social Media Marketing Activities and Purchase Intention: A Case of A Local Brand That Go-Global During Pandemic - Yusuf Ramadhani, Jenial; Prasasti, Arum (Indonesian Journal of Business and Entrepreneurship, 2023)
Indonesia has an active number of social media users, as many as 191 million people in January 2022 which rise significantly during the pandemic. This study aims to understand how social media marketing activities affect consumer purchase intention that is mediated by brand trust in a go-global, local clothing brand. This study uses a quantitative method on 200 respondents through an online questionnaire that is distributed to the Instagram followers of one of the go-global brands that showcase their product in New York Fashion Week in 2021. The results of this study indicate that social media marketing activities and brand trust have a significant effect on purchase intention. Brand trust mediates the relationship between social media marketing and purchase intention. Four dimensions of social media marketing activities namely word-of-mouth, entertainment, customizations, and trendiness, are the indicators that have the most significant influence in influencing purchase intention through brand trust. This research found two main things. First, social media marketing activities affect consumer purchase intentions to buy the product. Second, brand trust strengthens the influence of social media marketing activities on purchase intention. Keywords: social media, brand trust, word-of-mouth, purchase intention, pandemic